(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To identify in the literature the contributions of the use of the human placenta in the healing of foot ulcers in people with diabetes. Method: An integrative review study carried out by searching articles in Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Scientific Electronic Library Online (SciELO), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library, National Library of Medicine (PubMed), Web of Science and Scopus, using the search strategies: Placenta AND “Diabetic foot” and Placenta AND “Diabetic Foot”. Results: The initial search resulted in 148 articles. After applying the inclusion and exclusion criteria, a final sample of 12 articles was obtained. It was observed that the placenta has the potential to promote the improvement of granulation tissue and peripheral circulation, greater epithelialization, and reduction in the wound area, with the majority use of cryopreserved placental and amniotic membrane allograft. Conclusion: The human placenta is a nutrient-rich biological material that has the potential to contribute to the tissue repair of foot ulcers in people with diabetes in a shorter period of time.